2015
DOI: 10.1136/jramc-2015-000441
|View full text |Cite
|
Sign up to set email alerts
|

The prehospital management of avalanche victims

Abstract: Avalanche accidents are frequently lethal events with an overall mortality of 23%. Mortality increases dramatically to 50% in instances of complete burial. With modern day dense networks of ambulance services and rescue helicopters, health workers often become involved during the early stages of avalanche rescue. Historically, some of the most devastating avalanche accidents have involved military personnel. Armed forces are frequently deployed to mountain regions in order to train for mountain warfare or as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…10 The victims killed by nontraumatic causes gradually experience hypoxia, hypercapnia, and hypothermia. 12 Of the victims presented in the study, 40 were found dead after the incidence, and one casualty died after an admission to a secondary care hospital. The rate of mortality per total number of victims was 33.06%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…10 The victims killed by nontraumatic causes gradually experience hypoxia, hypercapnia, and hypothermia. 12 Of the victims presented in the study, 40 were found dead after the incidence, and one casualty died after an admission to a secondary care hospital. The rate of mortality per total number of victims was 33.06%.…”
Section: Discussionmentioning
confidence: 97%
“…The data dramatically vary depending on the area's topographic structure, the composite structure of snow, and the incident site being a forested or rocky terrain. 12 The avalanche victim can hit trees and rocks and fall down a cliff while rolling in a large mass of snow. 6,8 Of avalanche deaths, 57% are caused by internal and 43% are caused by external injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, control of major hemorrhages as an integral part of the triage process emerged as a recurrent topic in the included PHLSDC references, with a special emphasis on the role of non-medical bystanders, as specifically stressed by the Hartford Consensus after the Sandy Hook Elementary School mass shooting and by Lesaffre and colleagues after the 2015 Paris attacks [ 46 48 , 50 , 51 , 61 63 , 73 , 77 , 80 , 169 ]. Overall, attention was given to the importance of continuous real-time monitoring and re-assessment of casualties to guide prioritization of life-saving interventions and transportation, suggesting the possibility to introduce deployable technology, provided it to be quick, reliable, and easy to use [ 48 , 50 , 54 56 , 63 , 69 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%